Coercive, enabling, diagnostic, and interactive control: Untangling the threads of their connections. Issue 1 (December 2019) - Bisbe, Josep; Kruis, Anne-Marie; Madini, Paola
Abstract: Recent accounting research has connected the coercive and enabling types of formalisation (C/E) (Adler and Borys, 1996) with the distinction between diagnostic and interactive controls (D/I) proposed by Simons (1995, 2000) to tackle research questions on complex control situations involving both the degree of employee autonomy and patterns of management attention. The diverse conceptual approaches used for connecting C/E and D/I have led to fragmentation in the literature and raise concerns about their conceptual clarity. In this paper, we assess the conceptual clarity of various forms of connection between C/E and D/I. Firstly, we conduct an in-depth content analysis of 59 recent papers, and inductively identify three points of conceptual ambiguity and divergence in the literature (namely, the perspective from which a phenomenon is studied; whether categories capture choices driven by design or by style-of-use; and the properties of control systems). We also observe that the literature proposes various forms of connection (i.e. coexistence, inclusion, and combination approaches). Secondly, we use the three detected points of ambiguity and divergence as assessment criteria, and evaluate the extent to which conceptual clarity is at risk under each form of connection. Based on this assessment, we provide guidelines to enhance the conceptual clarity of the connections between C/E and D/I, propose several research models, and indicate opportunities for future research in this area.